Critical information infrastructures security : 10th international workshop, CRITIS 2015, Berlin, Germany, October 5-7, 2015 : revised selected papers /: 10th international workshop, CRITIS 2015, Berlin, Germany, October 5-7, 2015 : revised selected papers. (2016) - Unknown
No abstract available